Avaliação microbiológica de queijo de coalho comercializado na feira livre de Sousa - Paraíba - Diego Ernani Leite Bezerra; Carlos Roberto Marinho da Silva Filho; Damião Júnior Gomes; Ednaldo Barbosa Pereira Junior (Revista Principia, 2017)
For many years the curd cheese has stood out on the table of Brazilian consumers, especially in the Northeast due to its high nutritional value and its good taste and because of that it has been used in numerous dishes of the Northeastern cuisine. The aim of this study was to evaluate the microbiological quality of the curd cheese sold at a market garden in the city of Sousa-PB. Twenty curd cheese samples were collected every week during the month of October 2015, in five sales areas at a market garden in the city. Samples were analyzed at the Microbiological Analysis of Foods Laboratory of the Agroindustry sector at the Federal Institute of Education, Science and Technology of Paraíba, Campus Sousa, having as reference the Resolution of the Collegiate Board (RDC) n ° 12 of the National Sanitary Surveillance Agency. According to the results, the values obtained for total coliforms were considered high in almost all the samples. Regarding coliform, seven out of twenty samples (35%) were above the threshold count allowed by Brazilian law. As for the pathogenic to 65% of the samples presented coagulase positive Staphylococci counts and in 40% the growth of Salmonella sp,it was confirmed. Based on the results obtained,it can be said that these products are being manufactured without the adoption of Good Manufacturing Practices, which a condition that compromises the quality of the product and puts the health of consumers at risk